Experience of parents receiving results from a quality‐of‐life study in pediatric advanced cancer: A report from the PediQUEST study. Issue 9 (17th June 2019) - Bilodeau, Madeline; Dussel, Veronica; Wolfe, Joanne
Abstract: Little is known about the experience of parents receiving results of quality‐of‐life research in pediatric advanced cancer. The PediQUEST study participants who indicated interest in results during enrollment were mailed summarized findings and the Disseminating Quality‐of‐Life Research Questionnaire. Respondents (86%, 12/14) reported feeling more than "a little" recognized, grateful, or satisfied to receive results. Concurrently, 43% (6/14) endorsed feeling more than "a little" sad, confused, or anxious. Nonetheless, 81% (13/16) prefer to be informed in the future. Although parents experience a spectrum of strong emotions, our findings suggest quality‐of‐life study results should be shared.